Sustainable tourism village development model in five tourist villages in super priority destinations in Indonesia - Ningsih, Rezka Aida Patriasti Seja Purnama; Sunarta, I Nyoman; Suardana, I Wayan; Arida, I Nyoman Sukma (Research Journal in Advanced Humanities, 2025)
The development of Super Priority Destinations (DSP) is a form of embodiment of the National Tourism Development Master Plan (RIPPARNAS) for 2010 - 2025. During the COVID-19 pandemic, President Jokowi directed the Ministry of Tourism and Creative Economy to focus on developing 5 DSPs first, consisting of Tourism Villages in Lake Toba (North Sumatra), Borobudur (Central Java), Mandalika (West Nusa Tenggara), Labuan Bajo (East Nusa Tenggara), and Likupang (North Sulawesi). The development of 5 DSPs was carried out as a pilot project in the tourism village development program, which the village believes is the spearhead of development, so that one of the indicators of development success is realized from the prosperity of residents in the village. The development of tourist villages is carried out continuously. This study aims to determine the advantages and weaknesses of the sustainable tourism village development program in 5 advanced tourism villages in DSP in Indonesia by providing input on the appropriate model to be applied to these 5 destinations. The program is carried out by the government to attract tourists to visit, so that it can increase the number of tourists. The research method used in this study is qualitative. The data collection techniques that will be used are observation, interviews, documentation studies, and triangulation. The data analysis technique that will be used is NVIVO 12 Plus software. The technique for presenting the results of data analysis to be used is the Miles and Huberman model. The results of the study show that the best model of the five tourist villages in Super Priority Destinations in Indonesia is Waerebo Tourism Village, located in Labuan Bajo (East Nusa Tenggara). Therefore, every manager of a developed tourism village in DSP needs to improve its development model in order to increase the number of achievements based on the Sustainable Development Goals (SDGs). Waerebo Tourism Village needs to maintain the quality of service that involves the local community, so that tourists who have visited can visit again and invite colleagues and even relatives to visit. The Meat Tourism Village needs to be improved because tourists are crowded only during festivals and International Events. Sade Tourism Village needs to provide traditional house homestays so that tourists who come to visit have a longer time to enjoy the uniqueness of the village. Wanurejo Tourism Village needs to increase collaboration in tourism development in the 9 hamlets that are included in the village area. Bahoi Ecotourism Village needs to carry out continuous promotions to attract tourists to visit.